Arsenic and metal quantities in abandoned arsenide tailings in dissolved, soluble, and volatile forms during 20 years of storage; Chemical Geology; Vol. 568 - Bortnikova S. B. Svetlana Borisovna; Yurkevich N. V. Nataliya Viktorovna; Gaskova O. L. Olga; Volynkin S. S. Sergey Sergeevich; Edelev A. V. Aleksey Viktorovich; Grakhova S. P.; Kalnaya O. I.; Khusainova A. Sh.; Gora M. P.; Khvaschevskaya A. A. Albina Anatolievna; Saeva O. P.; Podolinnaya V. A. Valentina Alekseevna; et al. (2021, 2021)
Title screen